PENGARUH KOMITMEN ORGANISASIONAL, KEPUASAN KERJA, DAN KEPERILAKUAN ETIS TERHADAP KEINGINAN BERPINDAH PROFESIONAL SISTEM INFORMASI - Irwansyah, Irwansyah (Magister Manajemen, Fakultas Ekonomika dan Bisnis Undip, 2005)
The objective of this study is to determine the effects of organizational commitment, job satisfaction and ethical behavior to professional turnover intention in information system. This research is using survey method. Population in this research is all professional / worker of information system or laboring employees in the field of information system. Result of research is support that organizational commitment, job satisfaction and ethical behavior have the influence to profesional turnover intention in information system.